1997
DOI: 10.1073/pnas.94.17.8959
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal tail of histone H2A binds to two distinct sites within the nucleosome core

Abstract: Each of the core histone proteins within the nucleosome has a central ''structured'' domain that comprises the spool onto which the DNA superhelix is wrapped and an N-terminal ''tail'' domain in which the structure and molecular interactions have not been rigorously defined. Recent studies have shown that the N-terminal domains of core histones probably contact both DNA and proteins within the nucleus and that these interactions play key roles in the regulation of nuclear processes (such as transcription and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
1
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 44 publications
7
64
1
1
Order By: Relevance
“…This position is located at the junction of the H2A N-terminal tail and the histone fold domain, near the inside of the superhelical DNA gyre, and therefore is less likely to participate in inter-nucleosomal DNA binding (3,(5)(6)(7)58). Previous experiments have shown that irradiation of mononucleosomes containing H2A-A12C-APB results in crosslinks to DNA located ϳ40 bp to either side of the nucleosome dyad, consistent with the known structure of this complex (3,19). Similar to the previous experiment the HindIII end of nucleosome 1 in the dinucleosome was radiolabled, and H2A-A12C-APB was incorporated into nucleosome 2.…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations
“…This position is located at the junction of the H2A N-terminal tail and the histone fold domain, near the inside of the superhelical DNA gyre, and therefore is less likely to participate in inter-nucleosomal DNA binding (3,(5)(6)(7)58). Previous experiments have shown that irradiation of mononucleosomes containing H2A-A12C-APB results in crosslinks to DNA located ϳ40 bp to either side of the nucleosome dyad, consistent with the known structure of this complex (3,19). Similar to the previous experiment the HindIII end of nucleosome 1 in the dinucleosome was radiolabled, and H2A-A12C-APB was incorporated into nucleosome 2.…”
Section: Resultsmentioning
confidence: 51%
“…The proteins were checked by SDS-PAGE and trial reconstitutions. APB modification of H2A-G2C, H2B-2C, H3-T6C, and H4-G6C was carried out as previously described (19,55).…”
Section: Preparation Of Native and Apb-modified Histones-recombinantmentioning
confidence: 99%
See 2 more Smart Citations
“…Nucleosome Reconstitution-Recombinant Xenopus H2A and the cysteine-substituted mutant H2BG26C were prepared as preformed dimers, and the latter was modified with 4-azidophenacyl bromide (APB, 2 Sigma) as described (37,38). Histone H3/H4 tetramers were prepared from chicken erythrocyte nuclei, and nucleosomes were reconstituted with either native H2A/H2B or H2A/H2BG26C-APB.…”
Section: Methodsmentioning
confidence: 99%